Covering up Disfigurement and Laughing it Off: Reinforcing Inequality in Breast Cancer Support Groups. Issue 1 (25th August 2016) - Clark, Jacqueline
Abstract : The present study examines how women in breast cancer support groups managed the emotions evoked by the physical disfigurement of their disease and its treatment. Four support groups located in central North Carolina were studied over an approximately three‐year period. Data derive from field observation of the four groups, in addition to 35 in‐depth interviews with group members and group leaders. Analysis shows how the women concealed their disfigurement, practiced compensatory femininity, and engaged in sexualized joking to cope with the embarrassment, shame, and self‐doubt resulting from changes to their bodies, including the loss of a breast and sometimes hair. While these strategies seemed to help the women feel better about themselves and their bodies, at least some of the time, analysis also shows how the strategies contributed to the reproduction of gender inequality, by reinforcing traditional standards of beauty and the gendered expression of emotions.